Marie Curie for kids : her life and scientific discoveries, with 21 activities and experiments - O'Quinn, Amy M. (--for kids (Chicago, Ill.), 2017)
"Marie Curie, renowned for her work on radioactivity, was the first woman to win a Nobel Prize, the first person to win in two fields (chemistry and physics), and the first woman to hold a chair position at the Sorbonne. Marie Curie for Kids details Curie's remarkable life, from her childhood under a repressive czar in Poland to her tireless work supporting herself through college to meeting her ideal match in scientist Pierre Curie to her revolutionary research. Kids learn how Curie quietly flouted societal norms, working in full partnership with her husband while also teaching and raising two daughters. Scientific concepts are presented in a clear, accessible way, and a range of activities--from making Polish pierogi to exploring magnetism to using electrolysis to split water--allow for exploration of Curie's life, times, and work."--